Analysis of the Use of Bio Flap on NACA 4415 with Numerical Methods: Analisis Penggunaan Bio Flap pada NACA 4415 dengan Metode Numerik - James Julian; Saphira Anggraita Siswanto; Fitri Wahyuni; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2023)
This study was conducted using the Computational Fluid Dynamics (CFD) method using the Reynolds Averaged Navier Stokes (RANS) approach. The type of airfoil used in this study is the asymmetry NACA 4415 airfoil type. In this paper, computational tests were carried out on the airfoil with the addition of bionic flaps on its trailing edge. This study's update tests three variations of the Reynolds number: Re = 106, Re = 5 × 105, and Re = 3 × 105. The airfoil test was carried out at AoA 0°–25°. The addition of bionic flaps causes a decrease in lift performance at low AoA, but at high AoA, it can increase lift performance on airfoils. In addition, adding a bionic flap on the airfoil can delay the occurrence of a stall. At AoA 10°–13°, the Cd of the three variations of the Reynolds number experiences an increase in performance. Then, from this computational test, the resulting Coefficient moment (Cm) is a pitch down because the torque is below zero.